Do globalization and nuclear energy intensify the environmental costs in top nuclear energy-consuming countries?. (February 2023) - Sadiq, Muhammad; Shinwari, Riazullah; Wen, Fenghua; Usman, Muhammad; Hassan, Syed Tauseef; Taghizadeh-Hesary, Farhad
Abstract: Nuclear energy is considered an effective alternative to ensure global energy safety, and it has recently started to be promoted as a climate change mitigation solution to achieve low-carbon energy transition targets. Considering this view, this study aims to assess the environmental cost reduction by using nuclear energy efficiency and technological innovation from the prospects of the globalization process. Therefore, the relationship among carbon emissions, nuclear energy, globalization, and technological innovation was assessed in the top ten nuclear energy-consuming countries from 1990 to 2017 while controlling for economic growth and renewable energy. This study applied Common Correlated Effects Mean Group (CCEMG), Augmented Mean Group (AMG), and Dumitrescu-Hurlin causality techniques for model estimation that solves the problem of cross-sectional dependence and slope heterogeneity. The empirical results indicated that nuclear energy and technological innovation diminish environmental costs by reducing carbon emissions. However, globalization increases environmental costs by releasing more carbon emissions into the atmosphere. Moreover, bidirectional causality exists among nuclear energy, renewable energy, and carbon emissions. Consequently, the highest nuclear energy-consuming countries must utilize nuclear energy efficiency to control environmental costs and a cost-effective path to a low-carbon economy. Finally, this perspective intended to appeal to policymakers to do a better job of substantiating their decisions. Highlights: We applied novel panel data methods such as AMG, and CCEMG estimators. Empirical results explore long-run cointegration in the environment function. Nuclear energy, renewable energy and technology protect environmental quality. Globalization and economic growth degrade the environmental sustainability. Bidirectional causality exists between carbon emission, nuclear, and renewable energy.